The big stretch : 90 days to expand your dreams, crush your goals, and create your own success - Warner, Teneshia Jackson (McGraw Hill-Ascent Audio, 2019)
From concept to reality in just 90 Days-The Big Stretch is a proven program for making your personal and professional dreams come true The Big Stretch delivers a four-tiered self-evaluation and empowerment program for jumpstarting a new business, new career, or new idea-and maintaining high levels of success long-term. One of today's most effective coaches for entrepreneurs, Teneshia Jackson Warner walks you through a "career workout" routine designed to move you from idea to goal. First, you'll learn what type of dreamer you are: Hobby, Career, Make-It-Happen, Activist, or CEO. Based on that, you will discover your Dreamer's Risk Tolerance and understand your Dreamer's Ancestry to help gauge how much time, support, and resources you can apply toward your Stretch goal. You'll then create a One-Year Dream Projection to develop clear, realistic goals. Finally, you'll begin your 90-Day STRETCH program involving weekly exercises to build and strengthen your "business physique." Whether you want to escape the grind of a 9-to-5 job, improve an existing business, or simply get your dreams off the ground, The Big Stretch provides the knowledge and insight you need to turn your ideas into reality.